Studies on the Coloured Components of Black Tea - MOHAMED, MOSTAFA A. (The Libyan Journal of Agriculture, 2023)
The present investigation was carried out to study some physico-chemical properties of the pigments of black tea after their isolation and fractionation. Tea samples from India, Cylon, as well as samples obtained by ration card from the local market in Egypt, were used for this purpose. The adulteration of tea, by adding some strange matters, (like iron powder) was also studied. It was found that black tea contains from 2.5% (Indian tea) to 3.03% (Cylon tea) colouring matter. The presence of iron powder, though increased the intensity of the colour in the visible region of spectra (7.8 times), it did not really change the character of the absorption spectrum in the UV-region. The results indicate that the tea colourants have an indicator property and contain various groups of chromophores and auxochromes, which have intense absorption in the UV spectra (272-275 nm). The elemental analysis of the isolated polymers of the Indian tea sample was as follows: C — 40.83; H 5.78; O — 41.91; N — 5.04; S — 3.94; inorganic residue — 2.50. An empirical formula for the repeating unit in these polymers was deduced as follows: C26 27 ^45 46 ^20 21 N3 S. The infrared spectrum of these polymers showed at least nineteen significant bands. Employing the gel filtration technique on a column of Sephadex G-25 the colourants isolated from Indian tea were separated into three fractions. One was of brown hue and highest molecular weight. The two others were of yellow hue and lower molecular weights. Spectroscopic examination was applied to the fractions obtained. The results obtained give an evidence that tea colourants contain thearubigins, theaflavins, degradation products of chlorophyll and monomeric catechins.